Nahdlatul Ulama Families and the Internalization of Children’s Religious Moderation in the Digital Era: A Case Study in Semarang - Muhammad Luthfilhakim (Journal of Nahdlatul Ulama Studies, 2025)
This study explores the role of Nahdlatul Ulama (NU) families in instilling the values of religious moderation (wasathiyah) in children in the digital era. In the context of a society increasingly exposed to extremist information flows, NU families function as key actors in safeguarding balanced religious understanding through exemplary parenting, interactive dialogue, and educational digital supervision. Using a qualitative case-study approach, data were collected through in-depth interviews, observations, and documentation involving NU families and local religious figures. The findings show that moderate Islamic values tawassuth (the middle path), tawazun (balance), iʿtidal (justice), and tasamuh (tolerance) are internalized through social learning processes that include observation, modelling, and positive reinforcement. In addition, charismatic figures such as NU kyai (clerics) play a strategic role as spiritual authorities guiding the community to maintain a tolerant and contextual understanding of Islam. In responding to digital-era challenges, NU families’ strategies are shown to be effective in shaping children’s inclusive and critical character while preventing the radicalization of religious understanding. This research contributes to the development of a family-based model of religious moderation education that is responsive to the digital era.